2022
DOI: 10.1177/15459683221145149
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Adaptation Associated with Peripheral Nerve Recovery in Neuralgic Amyotrophy: A Randomized Controlled Trial

Abstract: Background: Neuralgic amyotrophy (NA) is a common peripheral nerve disorder caused by auto-immune inflammation of nerves in the brachial plexus territory, characterized by acute pain and weakness of the shoulder muscles, followed by motor impairment. Recent work has confirmed that NA patients with residual motor dysfunction have abnormal cerebral sensorimotor representations of their affected upper extremity. Objective: To determine whether abnormal cerebral sensorimotor representations associated with NA can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Currently, in the literature, the rehabilitation process lacks certainty, but some elements seem effective and are widely used, such as neurodynamic techniques [ 20 ]. Recent studies have shown that a multidisciplinary approach appears valid in managing these patients, emphasizing the importance of sensorimotor recovery, including exercises for regaining upper limb proprioceptive abilities and motor imagery [ 9 , 10 ]. A factor that had a positive influence on the patient’s prognosis in this case report is his young age, motivation, active lifestyle, and adherence to the therapeutic plan (the patient attended all the scheduled sessions).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, in the literature, the rehabilitation process lacks certainty, but some elements seem effective and are widely used, such as neurodynamic techniques [ 20 ]. Recent studies have shown that a multidisciplinary approach appears valid in managing these patients, emphasizing the importance of sensorimotor recovery, including exercises for regaining upper limb proprioceptive abilities and motor imagery [ 9 , 10 ]. A factor that had a positive influence on the patient’s prognosis in this case report is his young age, motivation, active lifestyle, and adherence to the therapeutic plan (the patient attended all the scheduled sessions).…”
Section: Discussionmentioning
confidence: 99%
“…This aspect is crucial since 60% of patients have residual weakness 2–3 years after the onset of the disease; over 50% are limited by pain; 63% experience severe fatigue; and 82% face difficulties in daily activities [ 8 ]. Several strategies have recently been proposed for the rehabilitation of PTS patients, such as a structured multidisciplinary approach that has proven effective [ 9 , 10 ]. This case report shows, for the first time, through an objective strength evaluation system, how recovery can occur even after three years and the role that a progressive multimodal rehabilitation treatment can have in achieving outcomes.…”
Section: Introductionmentioning
confidence: 99%